PERLINDUNGAN MERK PADA INDUSTRI AIR MINUM DALAM KEMASANPERLINDUNGAN MERK PADA INDUSTRI AIR MINUM DALAM KEMASAN - Nadya Damanik; Aris Prio Agus Santoso; Aryono (Collegium Studiosum Journal, 2025)
This study aims to analyze the effectiveness of legal mechanisms in protecting trademarks in the Bottled Drinking Water (AMDK) sector, with a case study on the FURE brand as a micro, small, and medium enterprise (MSME) product. Employing a normative juridical method with statutory, conceptual, and case study approaches, this research reviews the implementation of Law No. 20 of 2016 on Trademarks and Geographical Indications, which adopts the constitutive principle and the first-to-file system. The findings reveal that while FURE has obtained valid trademark registration and exclusive rights, practical challenges persist, including limited internal legal literacy, inadequate market monitoring, and the lack of optimized digital protection strategies. These results indicate the need for proactive measures such as cross-class registration, online monitoring, and the strengthening of legal literacy among MSMEs. The study contributes practical recommendations for business actors and policy insights for government institutions to enhance trademark protection systems in Indonesia.